Pengaruh Model Pembelajaran Berdiferensiasi Terhadap Literasi Berbicara Pada Mata Pelajaran Bahasa Indonesia Siswa Kelas X SMAN 1 Pangkep - Nurul Amaliya Saleh; Haslinda Haslinda; Maria Ulviani (Lembaga Pengembangan Kinerja Dosen, 2023)
The main objective of this research is to find out whether there is an effect of the Differentiated Learning Model on Speaking Literacy in Indonesian Class X, SMAN 1 Pangkep. This study uses a quantitative approach to the type of experimental research. The population used in this study was class X SMAN 1 Pangkep by taking two sample classes, namely the experimental class was class X Amanah which had a total of 35 students and the control class was class X Creative which had a total of 36 students. The data collection technique used was; written test and speaking test, observation, and interview. Data analysis consists of Descriptive Statistics and Inferential Statistics.The results of this study indicate that there is a significant influence between the differentiated learning model and speaking literacy in Indonesian language class X at SMAN 1 Pangkep. As seen from the Mann Whitney test, information is obtained that the average control is 81.3056 with a standard deviation of 7.285 while for experiments, the average value is obtained -an average of 79.0571 with a standard deviation of 6.978. The mean difference of 2.2485 is positive, thus information is obtained that the control value is greater than the experimental value. Although the control is larger than the experiment, the sig. shows a number of 0.302, the value is > 0.05 where H0 is accepted and H1 is rejected, which means that there is no difference in the average control with the experiment. Based on information that the average control is 80,194 with a standard deviation of 6,440 while for the experiment, the average value is 90,028 with a standard deviation of 5,586. The mean difference of -9,834 is negative, thus information is obtained that the control value is smaller than the experimental value. Besides that, the value of sig. shows a number of 0.000, the value is <0.05 where H0 is rejected and H1 is accepted, which means that there is an average difference between the control and the experiment. This proves that the differentiated learning model in learning Indonesian has an influence compared to before using the differentiated learning model.